The influence of professionality, work culture and competence on the quality of services at the personnel and training agency of Lampung Province - Surya, Andi; Sagita, Holdin; WA, Armalia Reny; CN, Yudhinanto; Hasbullah, Hasbullah; Yulistina, Yulistina (Goodwood Publishing, 2024)
Purpose: This study aimed to examine whether professionalism, work culture, and competence, both partially and simultaneously, significantly influenced the quality of service at the Lampung Province Personnel and Training Agency. Methodology: This study employed a survey method using questionnaires as the main research instrument. The population consisted of 13,906 Civil Servants (PNS) who were service recipients at the Lampung Province Personnel and Training Agency Office (Central Statistics Agency of Lampung Province, 2024). A proportional random sampling technique was applied, and the data were analyzed using multiple regression to test the partial and simultaneous effects. The independent variables were professionalism (X1), work culture (X2), and competence (X3), and the dependent variable was service quality (Y). Results: The findings show that professionalism, work culture, and competence positively and significantly affect service quality. Moreover, when tested simultaneously, these three variables significantly improved service quality, thereby confirming all the proposed hypotheses. Conclusion: The study concludes that professionalism, supportive work culture, and competence are crucial for improving public service quality in the Lampung Province Personnel and Training Agency. Limitations: This study is limited to cross-sectional data and a single agency, restricting generalization. Future research should apply longitudinal and comparative approaches across different government institutions. Contribution: This research provides theoretical evidence of the determinants of service quality in regional institutions and offers practical guidance for policymakers in developing training, organizational culture, and competency-building programs.